Corrosion mechanism of BN-ZrO2 based side-dam by molten steel. Issue 9 (August 2022) - Qian, Fan; Guo, Hairong; He, Yuanhang; Liu, Guoqi; Li, Hualong; Yang, Wengang; Li, Hongxia; Khan, Sayed Ali
Abstract: BN-ZrO2 -based side-dam is a hot spot for research and application of the thin strip continuous casting process. The corrosion mechanism of BN-ZrO2 based side-dam by molten steel has been demonstrated using contemporary detection technologies and microscopic analysis (I) Amorphous generation: BN oxidizes and volatilizes quickly at first. Residual products and steel inclusions combine to create the amorphous, which serves as a mass transfer medium. (II) Dissolution-precipitation: the components of side-dam such as m -ZrO2, Al2 O3, etc., which undergo dissolution-precipitation mass transfer through the amorphous in the working layer to achieve dependent growth as enrichment between crystals such as m -ZrO2, corundum, and spinel. (III) Solid-phase skeleton formation: m -ZrO2, corundum, spinel, and other coarse-grained particles unite and form a skeleton, with amorphous filling the structure, generating a slag mass, and sintering primarily in the solid phase, which is increasing macroscopically.